Prophetic Education Management Paradigm; Construction of Planning Narratives in the Story of Prophet Musa and Prophet Khidir - Asykur, Muamar; Tang, Muhammad; Habibah, St.; Ismail, Ismail (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This research is based on the story in the Qur'an, which presents theological values and, at the same time, the values of social morality as an important message to be conveyed to humans. What happened to the story of Prophet Musa and Nabi Khidir provides new insights about explicit educational planning messages to be applied in educational activities. This study explores the concept of planning carried out by Prophet Musa and Nabi Khidir, which explicitly means planning. Therefore, this research focuses on how the planning narratology is constructed in the story of Prophet Musa and Nabi Khidir. This study uses a qualitative method of library research. This research uses a descriptive-analytical approach that is normative and historical, which is adapted to the literature sources. The data analysis technique uses the interpretation method or text interpretation. The study results indicate that the planning values presented in the story are; receiving, responding, valuing, organization, characterization by a value or value complex.